Pengaruh Model Pembelajaran Gallery Walk terhadap Communications Skill Siswa pada Pembelajaran IPS - Silvana, Regita Dwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of the Gallery Walk learning model on the Communication Skills of eighth-grade students in social studies at SMP Negeri 22 Bengkulu. The background of this study is based on the importance of Communication Skills as one of the 21st-century skills that students must possess to support active and collaborative learning processes. The research method used was a quantitative method with a quasi-experimental design (Non-equivalent Control Group Design). The study population was all eighth-grade students at a public junior high school in Bengkulu City, with two classes taken by purposive sampling: an experimental class and a control class. Data collection instruments used were observation sheets, questionnaires, and communication tests. The results showed a significant difference between the Communication Skills of students taught using the Gallery Walk model and those taught using conventional methods. This is evidenced by the t-test results, which obtained a significance value (Sig.) <0.05. Thus, it can be concluded that the Gallery Walk learning model has a positive effect on improving students' Communication Skills in social studies. Keywords: Gallery Walk, Communication Skills, Social Studies Learning, Grade VIII Students